Vocal music : its story told through the lives and works of its foremost composers - Ewen, David, 1907-1985. (New York : F. Watts, 1975)
Traces the development of vocal music through the ages in discussions of its composers and their works.
Includes index.
Keywords: Vocal music -- History and criticism -- Juvenile literature; Composers -- Juvenile literature; Vocal music; Composers